2004
DOI: 10.1016/j.jacc.2004.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Comparative accuracy of real-time myocardial contrast perfusion imaging and wall motion analysis during dobutamine stress echocardiography for the diagnosis of coronary artery disease

Abstract: The majority of inducible perfusion abnormalities occur at an intermediate phase of the stress test, without wall motion abnormalities. Myocardial contrast echocardiography provides better sensitivity than WMA, particularly in patients with submaximal stress and in identifying patients with multivessel CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
7

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(104 citation statements)
references
References 33 publications
6
91
0
7
Order By: Relevance
“…In recent years, myocardial contrast echocardiography has been demonstrated to be a feasible and accurate method for the evaluation of myocardial perfusion in many clinical settings (2)(3)(4)(5). In addition, the combination of intravenous contrast agents and RTMCE with application of high-mechanical index impulses for microbubble destruction followed by myocardial replenishment has permitted the quantification of myocardial blood flow (19,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, myocardial contrast echocardiography has been demonstrated to be a feasible and accurate method for the evaluation of myocardial perfusion in many clinical settings (2)(3)(4)(5). In addition, the combination of intravenous contrast agents and RTMCE with application of high-mechanical index impulses for microbubble destruction followed by myocardial replenishment has permitted the quantification of myocardial blood flow (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…The development of low-mechanical index imaging techniques that cause minimal microbubble destruction has permitted simultaneous analysis of myocardial perfusion and function in real time (2). Real-time myocardial contrast echocardiography (RTMCE) increases the sensitivity of dobutamine stress testing for the detection of coronary artery disease (3,4) and can distinguish between stunned and infarcted myocardium after acute ischemia (5). However, some concerns regarding the safety of this new imaging modality remain, mainly because some animal studies have demonstrated damage to the endothelial system in the presence of microbubbles and ultrasound (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have also used MCE in conjunction with dobutamine or vasodilator (adenosine or dipyridamole) stress to detect CAD with a sensitivity and specificity comparable with that of nuclear techniques (43)(44)(45). Two studies have demonstrated the incremental prognostic value of MCE over routine clinical assessment in risk-stratifying patients who present to the emergency room with chest pain syndromes (46,47).…”
Section: Myocardial Perfusionmentioning
confidence: 99%
“…The interobserver agreement on the presence of reversible perfusion defects on MCPI in our laboratory is 92%. The intraobserver agreement is 92% (27). The anterior septum, mid-posterior septum, anterior wall, and adjacent apical segments were assigned to the left anterior descending coronary artery (LAD).…”
Section: Echocardiographic Imagingmentioning
confidence: 99%
“…To date, studies of myocardial perfusion in diabetic patients were performed mainly with nuclear techniques (12,13). Myocardial contrast echocardiography is a newly introduced technique for the evaluation of myocardial perfusion in patients with suspected CAD (27)(28)(29)(30)(31)(32)(33)(34)(35). Real-time imaging using low mechanical index pulse sequence schemes enhances the detection of microbubbles and reduces microbubble destruction.…”
mentioning
confidence: 99%